Multi Point, High Sensitive Tactile Sensing Module for Robots and Devices - Buyuksahin, Utku; Kirli, Ahmet (IEEE, 2014)
Tactile sensing usually refers to a transducer that is sensitive to touch, force, or pressure like human skin. A tactile-sensing array can be considered as a coordinated group of touch sensors. Recently, there has been an increased interest in tactile sensors, yet, the desired level, compared to the human's sensing ability still could not be reached for terms like number of receptors at certain area. The unique and the most important contribution of this paper(1) is to increase the number of sensory receptors per cm(2) up to millions. The second and supplementary contribution is the development of a method that can acquire these millions of data with ease at low costs. The design illustrated in this paper proposes using change of density of light (level of brightness) due to the deformation on contact surface. The density of light enters sequent mathematical algorithms as the input, and step by step, displacement, force and pressure data is evaluated as the output
Keywords: tactile sensors; high spatial resolution; fiber optics; image processing; HAND; Engineering; Remote Sensing